Real-world guideline-based treatment of lung cancer improves short- and long-term outcomes and resection rate: A population-based study. (February 2020) - Helminen, Olli; Valo, Johanna; Andersen, Heidi; Lautamäki, Anna; Vuohelainen, Vilma; Sihvo, Eero
Highlights: Utility of recent lung cancer guidelines were tested in a population-based setting. Increased rate of physical evaluation, invasive staging and VATS occurred. Patients faced less complications and had shorter hospital stay. Despite higher resection rate, recurrence-free survival improved. Guideline-based therapy provides significant advances to patients with lung cancer. Abstract: Objectives: Recent guidelines for the treatment of lung cancer include comprehensive lists of recommendations for pre-operative risk evaluation, staging, and surgery. Our aim was to evaluate whether the implementation of these in a population-based real-world setting would improve outcomes. Materials and methods: All patients diagnosed with primary lung cancer in Central Finland and Ostrobothnia between January 1, 2006, and December 31, 2017, were identified from registry data ( N  = 2116), including patients who underwent surgical resection ( n  = 303). Data were divided into two periods, old and modern, according to which international guidelines were followed. Results: Between surgical patients of the old and modern periods, significant changes occurred in the rate of pre-operative stair climbing tests (3.7 % vs. 68.6 %, p  < 0.001), the use of positron emission computed tomography (18.7 % vs. 75.7 %, p  < 0.001), and invasive staging (3.7 % vs. 26.0 %, p  < 0.001). In surgery, the rate of VATS (2.2 % vs. 81.1 %, p  < 0.001), segmentectomy (1.5 % vs. 27.2 %, p  < 0.001), and extended resections (5.2 % vs. 13.6 %, p  = 0.015) increased. However, between these periods, the rate of pneumonectomy decreased from 7.5 % to 1.2 % ( p  = 0.005) and bilobectomy from 9.0%–1.8% ( p  = 0.004). The overall resection rate increased from 10.5%–19.7 %, mainly due to a higher number of high-risk patients (12.7 % vs. 34.3 %, p  < 0.001). Patients faced fewer major complications (21.6 % vs. 8.9 %, p  = 0.002) and had shorter hospital stays (9 days, IQR 7–11 vs. 5 days, IQR 3–7; p  < 0.001). In the modern period, patients underwent adjuvant therapy less often than in the old period (35.1 % vs. 22.5 %, p  = 0.015). Recurrence-free 5-year survival rate improved, however, from 64.0%–76.8% ( p  < 0.001). Conclusions: The introduction of guideline-based modern patient evaluation and treatment was associated with improved short- and long-term outcomes of lung cancer surgery.